The phenological stages of forestry species under the impact of climate change• Early data - Dimitra Papagiannopoulou; T Tsitsoni (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
Urban areas have a dual role in climate change· they are major contributors to climate change as they produce more than 70 percent of greenhouse gas emissions and they also accept the impact of it. Urban trees have great value in urban ecosystems because of their role as carbon sinks, so they contribute to climate change mitigation. The aim of this paper is to collect data about the impact of climate change on forestry species in urban areas via the science of phenology. In recent years, via phenology, the observation and study of the effects of climate change are possible, as there appears to be a shift in the start of biological events, and also a change in their duration. These changes in the seasonal activity of plants, from time to time, are a sensitive but perfectly visible indicator of changes in the functioning of ecosystems. Phenology refers to the recording of dates in which different phases of the plant's life cycle such as budburst, flowering, dormancy, and hibernation have been observed both in species and in plant communities. Temperature, solar radiation, and water availability are the three factors that affect plant phenology. To appreciate the impact of climate change on the phenological stages of forestry species, three Phenological Monitoring Areas (PMA) were created in three urban spaces in Thessaloniki, in December 2020, within the framework of the project LIFE CliVut (Climate Value of Urban Trees) LIFE18 GIC/IT/001217. Each PMA contains 20 species (10 species of trees and 10 species of shrubs), and 100 individuals (5 individuals per species). The monitoring of the phenological stages of the forestry species was carried out throughout a year on a weekly basis according to the protocol that was created in the frame of the project taking into consideration the BBCH scale.